Analisis Itikad Tidak Baik dalam Pendaftaran Merek: Tinjauan Hukum dan Implikasinya - Noor, Tajuddin; Zulkifli, Suhaila; Keliat, Venia Utami (Verdict: Journal of Law Science, 2025)
To prevent infringement and cancellation, trademarks, as a form of intellectual property, must be clearly distinguishable from one another. The process of trademark registration must comply with the procedures established by the Directorate General of Intellectual Property (DGIP), which serve as a formal basis for the recognition of legal ownership. Despite this, similarities between trademarks frequently occur, resulting in disputes that are often rooted in bad faith. This study examines the procedural aspects of trademark registration under Law No. 20 of 2016, the criteria for acceptance or rejection of a trademark application, and the mechanisms for resolving disputes arising from bad-faith registration. This research adopts a normative juridical approach, utilizing theories, legal concepts, and statutory frameworks that are relevant to trademark protection. Primary data were obtained through field observations and community interviews, while secondary data were collected from books, online databases, and prior research. The findings indicate that bad faith is characterized by the deliberate intent to imitate an existing registered trademark, which may cause economic loss or reputational damage to the rightful owner. The law further stipulates that applicants acting in bad faith may be subject to sanctions. In conclusion, trademark registration procedures are governed by Article 4 of Law No. 20 of 2016, which requires that a trademark possess distinctiveness. Applications that fail to meet this requirement may be rejected in accordance with Article 21. Available dispute-resolution mechanisms include deletion or cancellation of a registered mark, as well as the filing of infringement lawsuits.